Production and characterization of activated carbon from palm shell by using microwave heating method / Roozbeh Hoseinzadeh Hesas - Roozbeh , Hoseinzadeh Hesas (2014)
Activated carbon (AC) demonstrated significant adsorption of pollutants in gas and liquid phases due to its high micropore volume, large specific surface area, favorable pore size distribution, thermal stability, capability for rapid adsorption and low acid/base reactivity. Palm shell (agricultural waste) is used as a raw material in this study due to its inherent characteristics such as high carbon content, low ash, and almost negligible sulfur content. In the present work, microwave heating was applied instead of conventional heating techniques as a heat source of AC preparation. This method reveals higher sintering temperatures and shorter processing times which result in higher efficiency and more energy saving. The effects of significant parameters such as microwave radiation time and power level, different types of chemical and physical agents, chemical impregnation ratio and particle size in production of ACs were investigated. Accordingly, the effects of these variables on the structural and surface chemical properties of the ACs were explored. Several methods of characterization were utilized to examine the prepared ACs including nitrogen adsorption-desorption at -196 °C, proximate and ultimate analysis, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Moreover, CO2 adsorption at different temperatures and methylene blue (MB) adsorption were carried out. The response surface methodology was used to optimize the preparation conditions of palm shell based ACs with microwave heating methods by zinc chloride chemical activation. The influence of variances on MB adsorption capacity and AC yield was investigated. Based on the analysis of variance, microwave power and microwave radiation time were identified as the most influential factors for AC yield and MB adsorption capacity, respectively. In this study, effects of different heating methods of microwave and conventional on textural and surface chemical properties of the ACs were compared. The ZnCl2 chemical activation at different weight ratio of ZnCl2 to precursors were applied. The results indicated that for both the microwave and conventionally prepared samples, the BET surface area (SBET) is enhanced to a maximum value at optimum impregnation ratio and then decreased with further increases in the agent ratio. The total pore volume in the microwave samples increased continuously with increasing zinc chloride, while in the conventional samples, the total pore volume increased up to the optimum impregnation ratio and then decreased. Oil palm shell based ACs were also prepared using KOH as an activation agent under the microwave irradiation. The effects of the activation time, chemical impregnation ratio and microwave power on the AC properties were investigated. To study the effects of the nature of the physical agent, the impregnated precursors were activated under a flow of carbon dioxide or nitrogen. The results demonstrates that the CO2 activation requires a shorter activation time to reach the maximum SBET than the activation under N2 since CO2 reacts with the carbon to develop the porosity.